DESIGNING OVERVOLTAGE AND UNDERVOLTAGE TRIPPING CIRCUIT FOR DISTRIBUTED SYSTEM LOAD WITH GSM ALERT USING MICROCONTROLLER (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
The main aims of this project to alert the relay when some difference in supply power for shield electrical home equipment and industrial instrument under over-voltage and under-voltage. The chances of damaged electronic devices are more because the equipment is much conscious in different power supply. In this scenario, it needs an extra shield system to shield the instrument by a different power. With the voltage comparator integrated circuits decide the trip of relay system get function as the voltage differs higher than or down the set worth. The major profit by that it also shields the 3-phase device from 1-phase and variation of power in ac power waveform. In the coming days it also possible earth fault detection and protection.